Darkest hour [compact disc, unabridged] : how Churchill brought England back from the brink - McCarten, Anthony, 1961- (Harper Audio, 2017)
From the acclaimed novelist and screenwriter of The Theory of Everything comes a revisionist look at the period immediately following Winston Churchill's ascendancy to Prime Minister. Soon to be a major motion picture starring Gary Oldman.